Imaging Manifestations of Intrahepatic Reactive Lymphoid Hyperplasia: A Case Report and Literature Review - Zhang, Bingqian; Zou, Mingyue; Lu, Zengxin; Mao, Haijia; Huang, Ya’nan; Liu, Fang; Zhao, Zhenhua (Frontiers in Oncology, 2021)
Reactive lymphoid hyperplasia (RLH) of the liver is a rare benign disease. This article describes a 77-year-old female patient with RLH of the liver. The patient was admitted to the hospital due to atrial fibrillation. A liver tumor was incidentally found during abdominal enhanced CT. Further magnetic resonance imaging (MRI) and PET/CT showed four lesions in the liver. The imaging findings suggested hepatocellular carcinoma (HCC), but it was not consistent that the patient had no history of liver cirrhosis and hepatitis, and a variety of tumor markers were within the normal range. The largest lesion was surgically removed and microscopically diagnosed as RLH of the liver. The pathology included a large number of reactive hyperplastic lymphoid follicles. Immunohistochemical examination showed that the infiltrating lymphocytes were polyclonal. The authors believe that the perinodular enhancement on MRI, the obvious limitation of diffusion on DWI, the insignificant increase of SUVmax on PET-CT delayed phase, and the support of clinical data can help distinguish liver RLH from lymphoma and HCC.